Development of anxiety and depression inventory for secondary school students in Iran - Khesht Masjedi, Mahnaz Fallahi (2012)
The purpose of the study was: (1) To determine the validity of A&D Inventory to measure anxiety and depression in secondary schools; (2) To determine the reliability of A&D Inventory in measuring anxiety and depression in secondary schools. The participants constituted of 579 students from the secondary school, whom were selected from teenagers who live in north of Iran in 2011-2012. Item pool generation was guided by the operational definition of the construct measured by the two theories: First, the Tripartite Model, and the second theory is the cognitive content specificity. The instrument has been devised and validated through a scientific method to ensure its reliability and validity. The results provide evidence that the developed instrument achieved sound psychometric properties. The overall reliability value of Cranach’s Alpha was .87. Also by Using EFA, the Anxiety & Depression inventory (A&D inventory) construct produced two significant factors. The hypothesized two-factor model identified via EFA in the Study consisted of 32 items, with 16 items belonging to anxiety and 16 items to depression. The CFA results showed that the goodness-of-fit indices for the revised model were as follows: χ2 =2111.222, DF=403, CMIN/DF= 3.785, GFI=.920, CFI=.937, NFI=.912, TLI=.908 and RMSEA =.047; each of the indices was the threshold values. To assess the convergent, construct reliability (CR), average variance extracted (AVE) method and discriminant validity were obtained. The construct reliability of all latent variables in this study was 0.95 in anxiety and 0.97 in depression. The average variance extracted values of latent variables in this table were between 0.78 in anxiety and 0.81 in depression and the last, AVE was greater than the squared correlation that demonstrated satisfactory discriminant validity. Evidence for the convergent validity of the A&D Inventory demonstrated through its significant high correlation between anxiety items of A&D Inventory with BAI items were.80 and high correlation depression items of the A&D Inventory with BDI (.89). Divergent validity of the A&D Inventory was demonstrated through its significant low correlation anxiety items of the A&D Inventory with BDI (.45) and low correlation depression items of the A&D Inventory with the BAI (.41). The overall test-retest reliability value of Cranach’s Alpha was .90. The A&D Inventory is simple, brief, and easy to administer. Indeed, the entire 32-item A&D Inventory takes no longer to complete than other symptom measures. Overall,therefore, the A&D Inventory can provide differentiated symptoms between anxiety and depression in a very quick and efficient manner for Iranian secondary schools. The measurement invariance of the Model across samples was done to test the factorial validity of the instrument. There is no significant difference between male and female in this study. The results of this study suggest that the items do not measure differences between male and female respondents. Overall, therefore, the A&D Inventory can provide differentiated symptom assessment in a very quick and efficient manner for Iranian secondary schools.